2008
DOI: 10.1152/ajpcell.00574.2007
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-induced alkalinization by the Na+/H+ exchanger isoform 1 is mediated through phosphorylation of amino acids Ser726 and Ser729

Abstract: Apoptosis is a complex process essential for normal tissue development and cellular homeostasis. While biochemical events that occur late in the apoptotic process are better characterized, early physiological changes that initiate the progression of cell death remain poorly understood. Previously, we observed that lymphocytes, undergoing apoptosis in response to growth factor withdrawal, experienced a rapid and transient rise in cytosolic pH. We found that the protein responsible was the pH-regulating, plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…Defining the factor(s) that may trigger apoptosis, oxidative stress and autophagy in those biliary epithelial cells remains a major challenge. Previous reports on the association of oxidative stress, apoptosis-like cell death, and changes in the intracellular pH (pH i ) [67,68,69] may provide some clues.…”
Section: Autoimmunity and Pathogenesis Of Pbcmentioning
confidence: 99%
“…Defining the factor(s) that may trigger apoptosis, oxidative stress and autophagy in those biliary epithelial cells remains a major challenge. Previous reports on the association of oxidative stress, apoptosis-like cell death, and changes in the intracellular pH (pH i ) [67,68,69] may provide some clues.…”
Section: Autoimmunity and Pathogenesis Of Pbcmentioning
confidence: 99%
“…In vascular smooth muscle cells, angiotensin II stimulates NHE1 by ERK-dependent p38MAPK phosphorylation and, in pro-B cells, NHE1-mediated apoptosis is regulated by phosphorylation at amino acids T 718 , S 723 , S 726 , and S 729 (21). Interestingly, the mutation of S 726/729 to nonphosphorylatable alanine is protective against serum deprivation-induced cell death (22). In myocardial cells, Erk 1/2-dependent pathways are critical in the regulation of NHE1; Erk 1/2 phosphorylates NHE1 at S 770 and S 771 , while p90 rsk , a kinase downstream of Erk 1/2, phosphorylates NHE1 at S 703 and, by doing so, forms a 14-3-3 ligand binding site (18).…”
Section: Introductionmentioning
confidence: 99%
“…3B). While we previously showed that D1 cells transiently alkalinize 6–8 hours after IL-7 withdrawal due to the activity of the sodium hydrogen exchanger 1 (NHE1) [16], this is an active mechanism induced by apoptotic stimulus [45]. In contrast, the increased intracellular pH of SMoR cells was detectable in the presence of IL-7 and did not change even during IL-7 withdrawal.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular pH-dependent changes in fluorescence were measured by flow cytometry, using methods previously described [45,46]. To establish a pH calibration curve, a separate group of cells (D1, SMoR, primary C57BL/6 and BimKO) were re-suspended in high-potassium HEPES buffer (25 mM HEPES, 145 mM KCl, 0.8 mM MgCl2, 5.5 mM glucose, and DDH2O) at pH standards (5.9, 6.5, 7.0, 7.2, and 7.8) and nigericin (10 μM) added followed by BCECF-AM.…”
Section: Methodsmentioning
confidence: 99%